The Transcription Factors TCP4 and PIF3 Antagonistically Regulate Organ-Specific Light Induction of SAUR Genes to Modulate Cotyledon Opening during De-Etiolation in Arabidopsis - Dong, Jie (Plant Cell, 2019)
Light elicits different growth responses in different organs of plants. These organ-specific responses are prominently displayed during de-etiolation. While major light-responsive components and early signaling pathways in this process have been identified, this information has yet to explain how organ-specific light responses are achieved. Here, we report that members of the TEOSINTE BRANCHED1, CYCLOIDEA, and PCF (TCP) transcription factor family participate in photomorphogenesis and facilitate light-induced cotyledon opening in Arabidopsis (Arabidopsis thaliana). Chromatin immunoprecipitation sequencing and RNA sequencing analyses indicated that TCP4 targets a number of SMALL AUXIN UPREGULATED RNA (SAUR) genes that have previously been shown to exhibit organ-specific, light-responsive expression. We demonstrate that TCP4-like transcription factors, which are predominantly expressed in the cotyledons of both light- and dark-grown seedlings, activate SAUR16 and SAUR50 expression in response to light. Light regulates the binding of TCP4 to the promoters of SAUR14, SAUR16, and SAUR50 through PHYTOCHROME-INTERACTING FACTORs (PIFs). PIF3, which accumulates in etiolated seedlings and its levels rapidly decline upon light exposure, also binds to the SAUR16 and SAUR50 promoters, while suppressing the binding of TCP4 to these promoters in the dark. Our study reveals that the interplay between light-responsive factors PIFs and the developmental regulator TCP4 determines the cotyledon-specific light regulation of SAUR16 and SAUR50, which contributes to cotyledon closure and opening before and after de-etiolation.